Elizabethkingia meningosepticum (Chryseobacterium meningosepticum) Infections in Children - Mehmet Ceyhan; Melda Celik (International Journal of Pediatrics)
Chryseobacterium meningosepticum is a ubiquitous Gram-negative bacillus historically associated primarily with meningitis in neonates and a wide variety of infections in immunocompromised patients. Neonatal infections often occur as outbreaks with environmental contamination being the source. C. meningosepticum infections are not common but are clinically important because the organism is naturally resistant to multiple antibiotics. In this paper, we have reviewed the nosocomial outbreaks of C. meningosepticum in newborns and infants reported so far in the literature and overviewed the infection control interventions, treatment modalities, and prevention measures.